Adolescents' experience of offline and online risks: Separate and joint propensities. (March 2016) - Görzig, Anke
Abstract: Adolescence is a period of increased risk experience and ever more often these occur online. The current study aims to investigate whether adolescents' online and offline risk experiences are driven by the same general propensity to risks. Data from a representative study of N = 19, 406 (50% girls) internet-using 11–16 year olds ( M = 13.54, SD = 1.68) youth in Europe were subjected to the current analyses. Three confirmatory factor analyses were applied to measures of offline and online risk experiences (five each). A bi-factor model of a general risk factor and two specific factors of online and offline risks was shown to provide the best theoretical and empirical fit. All risk experiences loaded significantly on the general risk factor while additionally all offline risks loaded significantly on the offline risk factor. However, none of the online risks loaded significantly on the online risk factor. Online risks could not be explained by factors that go beyond a general propensity to experience risks suggesting that new technologies do not bring with them a new type of risk propensity driven by that environment. Interventions should target risk and protective factors that can account for adolescents' experiences across risk types (online and offline). Highlights: Examines whether the propensity to experience risks online or offline has a single or separate underlying factors. Risk experiences whether online or offline appear to be driven by the same underlying propensity. The propensity for offline risks shows additional independent contributions for this environment only. New technologies do not bring with them a new type of risk propensity driven by that environment. Intervention efforts for online risks should be combined with those for offline risks.